2017
DOI: 10.2207/qjjws.35.160s
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Temperature Measurement in Metal Inert Gas Welding Process by Using Two Color Temperature Measurement Method

Abstract: Droplet temperature for Metal Inert Gas welding process was measured by using optical pyrometry; two colors temperature measurement method. High speed color video camera was used to capture an image of metal droplet during transfer to base metal. As a result, the movement of an arc to cover the droplet from bottom half to the entire droplet by increase of welding current had allowed the change in droplet heating process from concentrated to uniform heating. The concentrated heating in globular transfer mode ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These differences can be attributed to the arc heating process which closely influenced the droplet temper ature. It is mentioned that the temperature largely affects the surface tension of the droplet [25][26][27].…”
Section: Droplet Surface Temperature Distributionmentioning
confidence: 99%
“…These differences can be attributed to the arc heating process which closely influenced the droplet temper ature. It is mentioned that the temperature largely affects the surface tension of the droplet [25][26][27].…”
Section: Droplet Surface Temperature Distributionmentioning
confidence: 99%
“…Fig. 2 shows the peak temperature of weld pool in conventional MIG welding and plasma MIG welding that was measured by using two-color temperature measurement method [6] [7]. The analysis results clearly showed that the weld pool peak temperature of conventional MIG welding was 2287 K and the one in plasma MIG welding was 1885 K. The temperature difference was about 400 K. It is suggested that the higher peak temperature of weld pool in conventional MIG welding shows the higher cooling rate.…”
Section: Resultsmentioning
confidence: 99%
“…The mono-colour IR camera uses a single emissivity value to convert the thermal images to absolute temperature [6,13]. This poses a difficulty in determining the accurate temperature from the thermal images of a mono-colour IR camera as emissivity values depend on temperature [13]. A twocolour thermal camera measures the spectral intensities at two different wavelengths within a narrow range of wavelength bands and can directly estimate the actual temperature irrespective of variations in emissivity values over the radiating surface [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This poses a difficulty in determining the accurate temperature from the thermal images of a mono-colour IR camera as emissivity values depend on temperature [13]. A twocolour thermal camera measures the spectral intensities at two different wavelengths within a narrow range of wavelength bands and can directly estimate the actual temperature irrespective of variations in emissivity values over the radiating surface [13][14][15][16][17][18]. The two-colour thermal cameras are recently used for monitoring melt pool surface temperature for GMA brazing [6], GMAW [14] and GTAW [15] processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation